Peran Core Self Evaluation dalam Memprediksi Persipan Pensiun - Widyowati, Arini; Hadjam, Noor Rochman (Universitas Ahmad Dahlan, 2014)
ABSTRACTThis study examines the role of core self evaluation on predicting retirement preparation of pre retirement employees. This research involves 50 pre retirement employee of the exploration section of “ X Company” who get pre retirement program on 2013. Retirement preparation scale is used to measure effort of the employee’s retirement planning and core self evaluation is measured through core evaluation scale. Results show that there is no significant effect of core self evaluation on retirement preparation (F = 0.581, p = 0.679, p > 0.05). Based on data analysis it indicated that core self evaluation does not have effect on retirement preparation. It’s mean that core self evaluation could not predict employee’s retirement preparation. Thera are non-motivational and cultural factors that affect employees’ intention on retirement preparation.Keywords: core self evaluation, emotional stability, self esteem, self efficacy, locus of control, retirement preparation